Pengembangan Sistem Pengelolaan Layanan Usaha dan Pelatihan FPTC (Studi Kasus: Food Production And Training Center) - Rahman Rulli Arjiansa; Denny Sagita Rusdianto; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The bakery is one of the most popular businesses in the culinary field and easy to keep up with the times. One of the bakeries that are running its business in the city of Malang is the FPTC (Food Production and Training Center) shop. At this time, the FPTC shop wants to improve the progress of the existing services in their shop. So that their bread business can develop. However, services at the FPTC shop related to the process of activities such as sales transactions, ordering, and training have not been efficient. The reason is that the sales transaction process is quite long, the delivery of product menu information and training requirements is not sufficient, the confirmation of approval for training takes too long. Therefore, to improve the services available in the shops in this study, this research aims to create a website-based business service management and training system for FPTC. the system created can help FPTC store employees to more easily manage services, and for customers to more easily access services, as well as improve efficiency in service processes. The FPTC business service management and training system will be built or developed using the waterfall development model. The system implementation is built using the CodeIgniter framework and the system has a payment gateway service. Tests carried out on a system that has been built consist of unit testing, integration testing, and validation testing. the results of all tests obtained a percentage value of 100% and the status is valid. Besides, the compatibility test shows that the system can run well in various browsers without any errors or problems.